Design, synthesis and evaluation of the multidrug resistance-reversing activity of pyridine acid esters of podophyllotoxin in human leukemia cells. Issue 18 (15th September 2016) - Zhang, Lei; Chen, Fan; Zhang, Zeguo; Chen, Yongzheng; Lin, Ya; Wang, Jing
Graphical abstract: Abstract: Multidrug resistance (MDR) is the main cause for chemotherapeutic failure in cancer treatment. To overcome MDR, a serious of pyridine acid esters of podophyllotoxin was synthesized and their antiproliferation activities were evaluated against two human chronic myeloid leukemia cell lines in vitro. Most of them exhibited potent growth inhibition with IC50 values in the nanomolar range as well as markedly reduced resistance factors. The most potent compound, Y8 exhibited an IC50 of 0.046 ± 0.003 μM against resistance K562/ADR cells, showing more significant than that of adriamycin and etoposide, respectively. Furthermore, Y8 efficiently triggered cell cycle arrest at S phase and simultaneously induced apoptosis in K562/ADR cells. Meanwhile, Y8 also regulated the expression levels of cell cycle- and apoptosis-related proteins. Additionally, Y8 stimulated the ERK1/2 signalling and reduced the expression of Pgp protein. Finally, on the basis of results obtained using U0126, an ERK1/2 inhibitor, the ERK1/2 signalling pathway was proposed for the multidrug resistance-reversing effect ofY8 in K562/ADR cells. Together, Y8 could be a novel potential MDR reversal agent for the treatment of drug-resistant leukemia.